Health Communication in the Age of AI: A Review of the Tsinghua Doctoral Research Forum - Gao, Yujing (The Journal of Medicine, Humanity and Media, 2025)
As digital technologies such as artificial intelligence (AI) become increasingly integrated into everyday life, their influence on audience research continues to expand. On July 8, 2025, the Tsinghua Doctoral Research Forum was convened as part of the 8th International Conference on “Medicine, Humanity, and Media” (MHM2025). The Forum, led by Associate Professor CHEN Liang from Tsinghua University’s School of Journalism and Communication, focused on “Health Communication in the Age of AI: Audience Psychological Mechanisms and Innovations in Communication Models.” Four scholars presented their latest research. Topics included the influence of the Third-Person Effect on misinformation correction behaviours during public health emergencies, a systematic review of digital addiction among older adults, the differential effects of stigmatized HIV/AIDS messages across communication platforms, and the impact of threat and efficacy appeals on health behaviour intentions. The studies applied diverse empirical methods—such as structural equation modelling, systematic reviews, and experimental designs—to investigate psychological mechanisms and intervention strategies.